2021
DOI: 10.3390/jcm10061309
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide-Resistant and Macrolide-Sensitive Mycoplasma pneumoniae Pneumonia in Children Treated Using Early Corticosteroids

Abstract: We have found that early corticosteroid therapy was effective for reducing morbidity during five Korea-wide epidemics. We evaluated the clinical and laboratory parameters of 56 children who received early corticosteroid treatment for pneumonia that was caused by macrolide-resistant Mycoplasma pneumoniae (M. pneumoniae) or macrolide-sensitive M. pneumoniae between July 2019 and February 2020. All subjects had dual positive results from a PCR assay and serological test, and received corticosteroids within 24–36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…73) Previous studies have reported that the macrolide-resistant M. pneumoniae (MRMP) rate has been rising continuously and rapidly in Korea. The MRMP rate in 2011 was 51.6-62.9%, 74,75) but 60-87% of children reportedly had the A2063G mutation during 2018-2020 in Korea, [76][77][78] which is in agreement with the findings of the present study. M. pneumoniae has a high prevalence in Asia,…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 92%
“…73) Previous studies have reported that the macrolide-resistant M. pneumoniae (MRMP) rate has been rising continuously and rapidly in Korea. The MRMP rate in 2011 was 51.6-62.9%, 74,75) but 60-87% of children reportedly had the A2063G mutation during 2018-2020 in Korea, [76][77][78] which is in agreement with the findings of the present study. M. pneumoniae has a high prevalence in Asia,…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 92%
“…Meanwhile, some other studies have demonstrated that MRMP pneumonia might respond to macrolide treatment, and there was no difference in clinical or laboratory variables between MRMP and MSMP pneumonia. 9,11,12 Additionally, coinfection with M. pneumoniae and other respiratory pathogens are common, but it is not wellknown whether coinfection is related to the severity of illness. 13 The complicated relationship between hospital admission and these different factors and their relative importance remains unclear in children with M. pneumoniae pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, misdiagnosis of the disease can lead to negative health consequences, psychological distress and financial costs. Therefore, it is very important to use a correct, accurate and timely diagnostic method for this disease (19).…”
Section: Discussionmentioning
confidence: 99%